2015
DOI: 10.1002/marc.201500292
|View full text |Cite
|
Sign up to set email alerts
|

Star‐Shaped Macromolecules with the Core of Hexakis‐(fluoren‐2‐yl)benzene and the Periphery of Pyridine: Synthesis and Application as Solution‐Processable Electron‐Transport Materials

Abstract: Three new star-shaped macromolecules with hexakis(fluoren-2-yl)benzene as the core and pyridine as the periphery (2Py-HFB, 3Py-HFB, and 4Py-HFB) are synthesized and characterized. The synthetic conditions of octacarbonyldicobat-catalyzed cycloaddition reaction for different alkyne precursors are investigated. The coordination interaction between the pyridine ring of alkyne precursor and the cobalt catalyst may result in very low yield of the cyclotrimerization product. However, with the increase of the catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In a continuation of this work, recently Yang and co-workers reported three fluorene-based, star-shaped HAB derivatives 32 a–c (Figure ) bearing very good electron-transporting pyridyl groups at the periphery. All three derivatives showed good thermal stability and high electron affinity.…”
Section: Hab Derivatives For Organic Light-emitting Diodesmentioning
confidence: 71%
“…In a continuation of this work, recently Yang and co-workers reported three fluorene-based, star-shaped HAB derivatives 32 a–c (Figure ) bearing very good electron-transporting pyridyl groups at the periphery. All three derivatives showed good thermal stability and high electron affinity.…”
Section: Hab Derivatives For Organic Light-emitting Diodesmentioning
confidence: 71%
“…Abdelhamid et al 94 reported the synthesis of poly(2,6dimethyl-4-phenyl-1,4-dihydropyridinyl)arenes 159a, 159b, 161a, 161b, 163a and 163b in good yields through reaction of tris-, tetrakis-, and hexakis(formylphenoxy methyl)benzenes 157a, 157b, 160a, 160b, 162a and 162b, respectively, with 3aminobut-2-enenitrile 158 in acetic acid at reux (Schemes 39-41). 97 Yin et al 98 reported the synthesis of star-shaped macromolecules 186a-c with hexakis(uoren-2-yl)benzene as the core and pyridine as the periphery. The synthetic strategy includes octacarbonyldicobalt-catalyzed cycloaddition reaction for different alkyne precursors 184a-c.…”
Section: Ssms With Alicyclic Coresmentioning
confidence: 99%
“…Three pyridine substituted star shaped ETMs 55–57 were reported by Yang et al for application in OLEDs as a solution processed electron transporter. 85 The ETMs 55–57 were synthesized via Diels–Alder reactions of cyclopentadienone with the acetylene unit to get the final compounds through cyclotrimerization. The UV-Visible absorption spectra for compounds 55–57 shows a strong absorption band at 330 nm, which could be instigated from the collective π–π* transition of the fluorene units.…”
Section: Applicationsmentioning
confidence: 99%